2015
DOI: 10.1515/psicl-2015-0021
|View full text |Cite
|
Sign up to set email alerts
|

Native and non-native uses of English modal particles. The case of "surely" and "for sure"

Abstract: It has frequently been noted that non-native speakers of English find it difficult to express their views with the appropriate degree of conviction. However, many of the problems which non-native speakers have with specific modal expressions are still waiting to be identified. The aim of this paper is to compare native and non-native (student) uses of two English epistemics: "surely" and "for sure". The students' uses are mostly examined with reference to PICLE (the Polish subsection of the International Corpu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Douglas Biber et al (1999) indicated sensitivity of then to the language mode, high frequencies of it being found in conversations, and to a lesser degree to genre, with fiction containing a relatively higher number of the word under examination than other written genres. A number studies have reported on the differences between non-native and native learner English , Pérez-Paredes 2010, Rozumko 2015). The previous studies of then in learner language have yielded controversial results.…”
Section: Introductionmentioning
confidence: 99%
“…Douglas Biber et al (1999) indicated sensitivity of then to the language mode, high frequencies of it being found in conversations, and to a lesser degree to genre, with fiction containing a relatively higher number of the word under examination than other written genres. A number studies have reported on the differences between non-native and native learner English , Pérez-Paredes 2010, Rozumko 2015). The previous studies of then in learner language have yielded controversial results.…”
Section: Introductionmentioning
confidence: 99%